PERANCANGAN USER INTERFACE APLIKASI PEMESANAN DAPOER MBAHH BERBASIS MOBILE DENGAN PENDEKATAN DESIGN THINKING UNTUK MENINGKATKAN EFISIENSI OPERASIONAL - Roestamadji, Inne Fitriyani; Kusnadi, Kusnadi; Fahrudin, Rifqi; Parman, Suhadi (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
This research aims to assist Dapoer Mbahh, a cafe and restaurant in Cirebon, in improving their current ordering system, which still relies on manual methods. With the increasing number of customers and the large area of the restaurant, the manual system has become inefficient. Therefore, a mobile-based ordering application has been designed to replace the manual system. The author will design the UI/UX of this ordering application to streamline the ordering process for customers and enhance the restaurant's operational efficiency. The research method used is Design Thinking, known as a comprehensive approach focused on creating solutions by deeply understanding user needs. This method involves five stages: Empathize, Define, Ideate, Prototype, and Testing.Keywords: Design Thinking, User Interface, Ordering system, Dapoer Mbahh.